Diseño y Construcción de Herramienta para Extracción de Manguitos de Fijación en Ejes de Aero-enfriador de Aceite y Gas para Stork Technical Services Holding BV - Rodriguez Orduz, Rigoberto; Vela Garcia, Hugo Neftali (Universidad Antonio Nariño, 2022)
This document presents the different stages of the project and the results obtained through the process of research and implementation of practical and theoretical knowledge for the development of a fixing sleeve extractor tool to be used during gear maintenance. from bearings to Air Coolers whose maintenance is a charge of Stork Technical Services Holding BV.